Metallic Iron for Water Treatment: Healing A Research Community - Chicgoua Noubactep (Journal of New Developments in Chemistry, 2014)
Despite two decades of intensive research on using metallic iron (Fe0) for environmental remediation and water treatment, basic concerns about their efficiency still prevail. This communication presents the basic idea of the view that challenges the prevailing paradigm on the operating mode of Fe0/H2O systems. The alternative paradigm is in tune with the mainstream science on aqueous iron corrosion. Its large scale adoption will enable a scientifically based system design and increase the acceptance of this already proven efficient technology.
Keywords: Adsorption